2017
DOI: 10.1590/s1677-5538.ibju.2015.0441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide inhibitors in mice with bladder outlet obstruction

Abstract: Purpose To investigate the lower urinary tract changes in mice treated with L-NAME, a non-selective competitive inhibitor of nitric oxide synthase (NOS), or aminoguanidine, a competitive inhibitor of inducible nitric oxide synthase (iNOS), after 5 weeks of partial bladder outlet obstruction (BOO), in order to evaluate the role of constitutive and non-constitutive NOS in the pathogenesis of this experimental condition.Materials and Methods C57BL6 male mice were partially obstructed and randomly allocated into 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…data). And, the effects of NO in pBOO have been studied . Major sites of NO release were the urothelium and afferent nerves; NO modulate in various parts of lower urinary tract functions.…”
Section: Domentioning
confidence: 99%
“…data). And, the effects of NO in pBOO have been studied . Major sites of NO release were the urothelium and afferent nerves; NO modulate in various parts of lower urinary tract functions.…”
Section: Domentioning
confidence: 99%
“…1 The cubic structure is stable at low temperature and in bulk ZnS it is converted to the high temperature stable hexagonal phase at temperatures above 1000°C, however, for nanocrystalline ZnS, a cursor molecule is then converted into the metal sulfide by a chemical reaction, in most cases initiated by a thermal treatment. Metal dithiocarbonates, also known as metal xanthates, belong to this class of materials and their use for the preparation of a wide range of metal sulfides, for instance, CdS, 24,25 ZnS, 26,27 NiS, 28 SnS, 29 PbS, 30 Ga 2 S 3 , 31 Bi 2 S 3 , 32 CuInS 2 , 33,34 CuSbS 2 , 35 and Cu 2 ZnSnS 4 36 is already reported. A further beneficial property of metal xanthates as precursors is that the conversion can take place via thermal treatment in solution, 37,38 solid state reactions in a matrix, 39,40 solvent-free melt reactions [41][42][43] or aerosol assisted chemical vapour deposition (AA-CVD) processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, another study demonstrated that selective inhibition of iNOS was related to a decrease in bladder capacity, although it did not significantly decrease of bladder weight in mice with BOO. Conversely, the inhibition of all 3 NOS isoforms has been reported to increase nonvoiding contractions and to decrease the bladder capacity [ 15 ], thereby worsening the bladder function. Thus, only iNOS could not reflect bladder changes.…”
Section: Discussionmentioning
confidence: 99%